PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF GALLERY WALK TERHADAP MOTIVASI BELAJAR PPKn SISWA KELAS X SMA NEGERI 12 PEKANBARU - Feri Fadli Fadli; Gimin '; Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study was motivated by the low motivation to learn PPKn student at SMAN 12 Pekanbaru. Formulation of the problem in this research is: "Is there any Influence Learning Model Gallery Walk Against Motivation PPKn Class X SMA Negeri 12 Pekanbaru?". This study aims to determine Is There Influence of Cooperative Learning Model Gallery Walk in Improving Learning Motivation PPKn Class X SMA Negeri 12 Pekanbaru ". This research was conducted in SMA 12 Pekanbaru in May 2015. This research is quantitative descriptive the population in this research is class X SMA Negeri 12 Pekanbaru. The sample in this study was based technique of "purposive sampling". Where classes are taken into the sample are students of class X MIA 2 (experimental grade) were given learning models Gallery Walk, and class X MIA 3 (control class) is a student who was given the conventional method and then the data analysis using the homogeneity test and test " t ". Based on the results of the study indicate that there are significant learning motivation among students who use learning models Gallery Walk and conventional methods in SMA 12 Pekanbaru (t = 8.9> table = 2.00). Where there is an average increase learning motivation PPKn experimental class of 22.87 into 30.13 and an average increase learning motivation PPKn control classes of 25.51 into 26.26. Thus the hypothesis which says there are significant learning model use Gallery Walk on motivation to learn PPKn class X SMA Negeri 12 Pekanbaru, unacceptable. Keywords: Gallery Walk, motivation to learn, lesson PPKn